PHENOMENOLOGICAL STUDY: THE MEANING OF ENTREPRENEURSHIP FOR COMMERCIAL EDUCATION ALUMNUS FACULTY OF ECONOMICS AND BUSINESS STATE UNIVERSITAS NEGERI MALANG - Dimas Putri Mega Pratesa; Cipto Wardoyo; Ely Siswanto (Pusat Riset dan Inovasi Nasional, 2022)
Seeing the important role of entrepreneurship in the Indonesian government's economy, universities in Indonesia have provided education on entrepreneurship for their students. It is intended that their students can become entrepreneurs after graduating from college. However, becoming an entrepreneur is not easy, because it requires strong motivation from within a person to start their own business. The decision to become an entrepreneur is also not popular because of the large responsibilities that must be borne by business owners. Therefore this study wants to see the meaning of entrepreneurship for an alumnus of Business Administration Education. This research was conducted using a qualitative phenomenological method. The results of this study state that several attitudes must be owned by an entrepreneur, challenges that must be faced by an entrepreneur, and the benefits of entrepreneurship. The subjects of this study were alumni of the Universitas Negeri Malang Faculty of Economics and Business Commerce Education who already have their businesses. This research is also expected to be able to provide additional contributions to material about entrepreneurship